2002
DOI: 10.1016/s0033-3549(04)50175-9
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of Escherichia coli O157: nonmotile infections associated with recreational exposure to lake water

Abstract: E. coli O157: NM infections were associated with swallowing water from a freshwater lake. Potential sources of contamination include feces from humans, cattle, or deer. This outbreak illustrates the value in screening patients with diarrhea for E. coli O157, submitting isolates to public health laboratories, and using molecular techniques to identify related cases. Outbreaks associated with contaminated freshwater could be averted by prevention and early detection of contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…In addition, these deer potentially could contaminate recreational or drinking waters. Indeed, wild deer have been implicated as the source of fecal contamination in human infections of Escherichia coli O157 associated with the consumption of venison (Keene et al, 1997;Rabatsky-Ehr et al, 2002) and were identified as one of the potential sources of fecal contamination in outbreaks of E. coli O157 associated with unpasteurized apple juice (Cody et al, 1999) and contaminated lake water (Feldman et al, 2002). In agricultural areas, deer feces could contaminate produce or livestock feed crops, and wild deer may have direct or indirect contact with food-producing livestock, particularly pastured livestock, resulting in bidirectional transmission.…”
mentioning
confidence: 99%
“…In addition, these deer potentially could contaminate recreational or drinking waters. Indeed, wild deer have been implicated as the source of fecal contamination in human infections of Escherichia coli O157 associated with the consumption of venison (Keene et al, 1997;Rabatsky-Ehr et al, 2002) and were identified as one of the potential sources of fecal contamination in outbreaks of E. coli O157 associated with unpasteurized apple juice (Cody et al, 1999) and contaminated lake water (Feldman et al, 2002). In agricultural areas, deer feces could contaminate produce or livestock feed crops, and wild deer may have direct or indirect contact with food-producing livestock, particularly pastured livestock, resulting in bidirectional transmission.…”
mentioning
confidence: 99%
“…Although most of the known outbreaks of E. coli O157:H7-associated disease in humans are food borne or waterborne, several recent studies indicate that a significant number of human infections are acquired from direct contact with cattle, the environment, or unknown sources (1,12,30,34). An accepted premise is that the reduction of the number of cattle infected with E. coli O157:H7 or the elimination of E. coli O157:H7 from cattle will effect a reduction in the rate of disease in humans.…”
mentioning
confidence: 99%
“…Contamination of drinking or recreational waters with enterohemorrhagic E. coli (EHEC) has resulted in an increase in the number of outbreaks and deaths from hemolytic-uremic syndrome in humans (11,28). Found in the gastrointestinal tract of cows, EHEC, which can carry stxI, stxII, and eaeA virulence genes, is transmitted by food or water supplies polluted with cow fecal waste.…”
mentioning
confidence: 99%